2002
DOI: 10.1034/j.1600-0749.2002.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Play a Regulatory Role in the Control of Pigmentation in Reconstructed Human Skin from Skin Types I and II

Abstract: Human melanocytes in monolayer culture are extremely dependent on a wide range of soluble signals for their proliferation and melanogenesis. The advent of three-dimensional models of reconstructed skin allows one to ask questions of how these cells are regulated within a setting which more closely approximates normal skin. The purpose of this study was to investigate to what extent melanocytes within a reconstructed skin model are sensitive to regulation by dermal fibroblasts, basement membrane (BM) proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 49 publications
(88 reference statements)
5
50
0
Order By: Relevance
“…Although cultured mouse melanocytes and melanoma cells reliably pigment to a-MSH addition (Eberle, 1988), human melanocytes have little or no response (Friedmann et al, 1990;De Luca et al, 1993;Hedley et al, 1998a). Responses relate to skin type (Hunt et al, 1994) with melanocytes from type 1 and type 2 skin donors rarely pigmenting to a-MSH in vitro, whether in 2-D (Hedley et al, 1998a) or 3-D culture (Hedley et al, 2002).…”
mentioning
confidence: 99%
“…Although cultured mouse melanocytes and melanoma cells reliably pigment to a-MSH addition (Eberle, 1988), human melanocytes have little or no response (Friedmann et al, 1990;De Luca et al, 1993;Hedley et al, 1998a). Responses relate to skin type (Hunt et al, 1994) with melanocytes from type 1 and type 2 skin donors rarely pigmenting to a-MSH in vitro, whether in 2-D (Hedley et al, 1998a) or 3-D culture (Hedley et al, 2002).…”
mentioning
confidence: 99%
“…It was recently reported that the hypopigmentation of palmoplantar skin (on the palms and soles) compared to nonpalmoplantar (trunk) skin in humans is regulated by dermal fibroblasts in those areas, specifically via a secreted factor (Dickkopf-related protein 1; DKK1) that regulates Wnt signaling (Yamaguchi et al, 2004;Yamaguchi et al, 2007b;Yamaguchi et al, 2008). Furthermore, several other studies have shown the influence of dermal fibroblasts on human epidermal pigmentation (Cario-Andre et al, 2006;Hedley et al, 2002). Therefore, we hypothesized that fibroblasts in the dermis of trunk skin play important functions in regulating the constitutive color of different phototypes of skin and their responses to the environment, particularly via the factors they secrete.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the melanin production in melanocytes is influenced by keratinocytes and fibroblasts. [23,24] Primary human melanocytes and keratinocytes have some drawbacks such as the limited proliferate capacity and the donor variability. Thus the use of immortalized cell lines would be more suitable for investigating the effects of pigmentation regulators.…”
Section: Discussionmentioning
confidence: 99%